Allan Hills Stable Water Isotopes - Kurbatov, Andrei V.; Spaulding, Nicole; Mayewski, Paul A.; Introne, Douglas (IEDA: US Antarctic Program Data Center, 2013)
Abstract: This data set includes stable water isotope values at 10 m resolution along an approximately 5 km transect through the main icefield of the Allan Hills Blue Ice Area, and at 15 cm within a 225 m core drilled at the midpoint of the transect.